Assessing the Nutritional-Value-Based Therapeutic Potentials and Non-Destructive Approaches for Mulberry Fruit Assessment: An Overview - Manzoor, M. F.; Hussain, A.; Tazeddinova, D.; Abylgazinova, A.; Xu, B. (Computational Intelligence and Neuroscience. - 2022, 2022)
Among different fruits, mulberry is the most highlighted natural gift in its superior nutritional and bioactive composition, indispensable for continuing a healthy life. It also acts as a hepatoprotective immunostimulator and improves vision, anti-microbial, anti-cancer agent, anti-stress activity, atherosclerosis, neuroprotective functions, and anti-obesity action. The mulberry fruits also help reduce neurological disorders and mental illness. The main reason for that is the therapeutic potentials present in the nutritional components of the mulberry fruit. The available methods for assessing mulberry fruits are mainly chromatographic based, which are destructive and possess many limitations. However, recently some non-invasive techniques, including chlorophyll fluorescence, image processing, and hyperspectral imaging, were employed to detect various mulberry fruit attributes. The present review attempts to collect and explore available information regarding the nutritional and medicinal importance of mulberry fruit. Besides, non-destructive methods established for the fruit are also elaborated. This work helps encourage many more research works to dug out more hidden information about the essential nutrition of mulberry that can be helpful to resolve many mental-illness-related issues Среди различных фруктов шелковица является самым выдающимся природным подарком благодаря своему превосходному питательному и биологически активному составу, незаменимому для продолжения здоровой жизни. Он также действует как гепатопротекторный иммуностимулятор и улучшает зрение, обладает антимикробным, противораковым средством, антистрессовой активностью, атеросклерозом, нейропротекторными функциями и действием против ожирения. Плоды шелковицы также помогают уменьшить неврологические расстройства и психические заболевания. Основной причиной этого является терапевтический потенциал, присутствующий в питательных компонентах плодов тутового дерева. Существующие методы оценки плодов шелковицы в основном основаны на хроматографии, которая является деструктивной и имеет много ограничений. Однако в последнее время некоторые неинвазивные методы, в том числе флуоресценция хлорофилла, обработка изображений и гиперспектральная визуализация, использовались для обнаружения различных свойств плодов шелковицы. В настоящем обзоре предпринята попытка собрать и изучить доступную информацию о питательной и лечебной ценности плодов шелковицы. Кроме того, разрабатываются неразрушающие методы, установленные для плодов. Эта работа помогает стимулировать многие другие исследовательские работы, чтобы раскопать больше скрытой информации об основных питательных веществах шелковицы, которые могут быть полезны для решения многих проблем, связанных с психическими заболеваниями.
Keywords: импакт-фактор 2022; скопус; зарубежное издание; дальнее зарубежье; научный журнал; зарубежные авторы; шелковица; лекарственные растения; фармация